Measurement of 18 Perfluorinated Organic Acids and Amides in Human Serum Using On-Line Solid-Phase Extraction - Kuklenyik, Zsuzsanna; Needham, Larry L; Calafat, Antonia M (Analytical chemistry (Washington), 2005)
We have developed an on-line solid-phase extraction (SPE) method coupled to high-performance liquid chromatography (HPLC)−tandem mass spectrometry (MS/MS) for measuring trace levels of 18 perfluorinated chemicals (3 perfluorosulfonates, 8 perfluorocarboxylates, 7 perfluorosulfonamides) in serum. Without protein precipitation, only dilution with 0.1 M formic acid, one aliquot of 100 μL of serum was injected into a commercial column switching system that allowed for concurrent SPE and HPLC−MS/MS acquisition. First, the analytes were concentrated on a C18 SPE column. Then, this column was placed automatically in front of a C8 analytic HPLC column for chromatographic separation of the analytes. Detection and quantification were done using negative-ion TurboIonSpray ionization, a variant of electrospray ionization, MS/MS. Excellent recovery was achieved for all analytes including the volatile sulfonamide derivatives that could not be determined before using traditional off-line SPE methods. The high throughput and low limits of detection (0.05−0.8 ng/mL) using a small sample volume (100 μL of serum) and isotope dilution quantification make this method suitable for large-scale epidemiologic studies.